Adaptation of Foxtail Millet (Setaria italica L.) to Abiotic Stresses: A Special Perspective of Responses to Nitrogen and Phosphate Limitations - Nadeem, Faisal; Ahmad, Zeeshan; Ul Hassan, Mahmood; Wang, Ruifeng; Diao, Xianmin; Li, Xuexian (Frontiers in Plant Science, 2020)
Amongst various environmental constraints, abiotic stresses are increasing the risk of food insecurity worldwide by limiting crop production and disturbing their geographical distribution. Millets are known to possess unique features of adverse environment resilience especially under infertile soil conditions although underlying mechanisms are yet to be determined. The small diploid genome, short stature, excellent seed production, C4 photosynthesis and short life cycle of foxtail millet make it a very promising model crop to study nutrient stress responses. Foxtail millet, known to be a drought tolerant crop, responds to low nitrogen and low phosphate by respective reduction and enhancement of its root system. Such special response of foxtail millet is quite different to what shown by maize and some other cereals. In contrast to a smaller root system under low nitrogen, foxtail millet enhances biomass accumulation facilitating root thickening presumably for nutrient translocation. The low phosphate response of foxtail millet links to the internal nitrogen status which tends to act as a signal regulating the expression of nitrogen transporters and hence indicates its inherent connection with nitrogen nutrition. Altogether, the low nitrogen and low phosphate responses of foxtail millet can act as basis to further determine the underlying molecular mechanisms. Here, we will highlight the abiotic stress responses of foxtail millet with a key note on its low nitrogen and low phosphate adaptive responses in comparison to other crops.